2022
DOI: 10.1371/journal.pone.0267143
|View full text |Cite
|
Sign up to set email alerts
|

Multi-methodological approach for the Quality assessment of Senecionis scandentis Herba (Qianliguang) in the herbal market

Abstract: We set forth to assess the quality of an herbal medicine sold in Hong Kong called Qianliguang by employing a multi-methodological approach. The quality is set by its identity, chemical composition, and bioactivities, among others. Qianliguang (Senecionis scandentis Herba, Senecio scandens Buch.-Ham. ex D.Don) has known antibacterial properties. However, it is poisonous and overconsumption can result in liver damage. Eighteen Qianliguang samples were purchased from herbal shops at various districts in Hong Kong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The luciferase In recent years, with the increasingly widespread bacterial resistance, the difficulty of treating Currently, TCM treatment has great advantages and characteristics, providing new ideas for clinical treatment in CAP. As a common TCM, S. scandens and its extracts and compounds possess diverse pharmaceutical activities, like anti-inflammatory, antibacterial and anticancer activities [6,10] . The petroleum ether extract of S. scandens could impede inflammatory response in LPS-stimulated RAW264.7 cells [11] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The luciferase In recent years, with the increasingly widespread bacterial resistance, the difficulty of treating Currently, TCM treatment has great advantages and characteristics, providing new ideas for clinical treatment in CAP. As a common TCM, S. scandens and its extracts and compounds possess diverse pharmaceutical activities, like anti-inflammatory, antibacterial and anticancer activities [6,10] . The petroleum ether extract of S. scandens could impede inflammatory response in LPS-stimulated RAW264.7 cells [11] .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, water extract of S. scandens could suppress Mas-Related G Protein-Coupled Receptor-B2 (MRGPRB2) receptor of mast cells to alleviate pruritus [5] . S. scandens has known antibacterial properties, and exhibits suppression on S. pneumoniae [6] . In addition, the ethanol extract of S. scandens could elevate MUC2 and sIgA, and maintain the diversity of gut microbiota [6] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Lo and colleagues (2018) [9] found that Hominis Placenta were adulterated by non-animal origins. In 2022, Ngai discovered that Senecionis scandentis Herba sold in eighteen districts were either toxic or adulterated [10]. The problems in the quality of herbs have endured regardless of negative business consequences.…”
Section: Introductionmentioning
confidence: 99%
“…The use of authentic herbs is important to ensure the beneficial effects and to avoid poisoning. Substitution frequently occurs due to the confusion of names and appearances [ 3 ], and the use of cheaper herbs [ 4 ] to reduce the cost. For example, herbal tea containing toxic Japanese Star Anise Illicium anisatum L. instead of non-toxic Chinese Star Anise Illicium verum Hook.f.…”
Section: Introductionmentioning
confidence: 99%